Biomass and carbon stock estimation of mangroves in Pulau Indah, Klang, Selangor / Muhamad Hafiz Afham Khaini - Khaini, Muhamad Hafiz Afham (2020)
Mangrove ecosystem is a natural fortress that acts as a defense mechanism for coastal communities helping mitigate climate change by sequestering and storing significant amounts of carbon. Globally, mangrove are threatened with reclamation and degradation for anthropogenic needs. The development plan of a biotech industry hub or “Selangor Bio Bay” (SBB) is expected to clear the remaining mangrove in Pulau Indah. The mangrove will be converted into industrial, residential and commercial unit. This study was conducted to determine the abundance of mangrove species, to estimate the mangrove biomass and carbon stock of the mangroves species and mangrove ecosystem at the proposed SBB project site in Pulau Indah, Klang, Selangor. Six mangrove species from three genera (Avicennia, Brugueira, Rhizophora) were recorded namely Avicennia alba, A. marina, Bruguiera gymnorhiza, B. parviflora, Rhizophora apiculata and R. mucronata. The abundance of the mangrove species in Pulau Indah specifically at the SBB development site were quantified through basal area (47.053 ± 22.938 m2 ha-1), density (906 ± 196 tree ha-1) and frequency of occurrence. R. apiculata recorded the highest frequency (100%) while A. marina recorded the lowest frequency (44%). The mean biomass of mangrove ecosystem in the study area was estimated at 253.162 ± 125.694 t ha-1 where total aboveground tree biomass was 185.411 ± 104.151 t ha-1 and belowground tree biomass was 60.718 ± 35.883 t ha-1. The ecosystem carbon stock for Pulau Indah was estimated at 867.808 ± 89.301 t C ha-1. This study concludes that Pulau Indah mangroves hold a significant amount of carbon where approximately 86% is stored as soil carbon and the 14% of carbon stock is held by other components within the mangrove ecosystem. Removing the remaining carbon reservoir in Pulau Indah, Klang will emit a significant amount of CO2-equivalent (509,576.857 t ha-1) to the atmosphere exacerbating global warming.